1996
DOI: 10.2307/2945841
|View full text |Cite
|
Sign up to set email alerts
|

Do Bills of Rights Matter? The Canadian Charter of Rights and Freedoms

Abstract: Although constitutional protection for rights is increasingly popular, there is little systematic research on the extent to which bills of rights affect the process of government. This article examines the effects a bill of rights may be expected to produce, and then uses a quasi-experimental design to analyze the effects of the Canadian Charter of Rights and Freedoms on the Canadian Supreme Court's agenda. The data suggest that the Charter indeed has influenced the Court's agenda, although the effects are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 36 publications
0
27
0
3
Order By: Relevance
“…After analyzing the Constitution Act of 1982, Russell (1982) concluded that the Charter had sanctioned a major shift of power from the legislature to the judiciary and, thus, judicial activism would necessarily follow. Indeed, subsequent studies have indicated that there are already signs of a more activist Canadian Court (Morton 1987;Morton et al 1994;Morton et al 1991;Knopff and Morton 1992;Manfredi 1993; Ostberg Epp 1996). In this debate, Verney (1987) and Monahan (1987) have argued that, instead of assuming that the Canadian Court would adopt the American style of judicial review, one must understand the changes taking place under the Charter in the Canadian culFural context.…”
Section: The Canadian Supreme Court Andmentioning
confidence: 94%
“…After analyzing the Constitution Act of 1982, Russell (1982) concluded that the Charter had sanctioned a major shift of power from the legislature to the judiciary and, thus, judicial activism would necessarily follow. Indeed, subsequent studies have indicated that there are already signs of a more activist Canadian Court (Morton 1987;Morton et al 1994;Morton et al 1991;Knopff and Morton 1992;Manfredi 1993; Ostberg Epp 1996). In this debate, Verney (1987) and Monahan (1987) have argued that, instead of assuming that the Canadian Court would adopt the American style of judicial review, one must understand the changes taking place under the Charter in the Canadian culFural context.…”
Section: The Canadian Supreme Court Andmentioning
confidence: 94%
“…Before the Charter, parliamentary sovereignty was the norm; generally speaking, courts were not seen as key policymakers (Snell and Vaughan 1985). Soon after the Charter was enshrined as a constitutional document, the Supreme Court of Canada began to assert itself, consistent with other legal changes in the 1970s facilitating judicial policy-making (Epp 1996). In terms of sexuality, this process took longer, especially given that the authors of the Charter explicitly rejected including sexual orientation in the list of protected classes in the Charter's equality section, Section 15 (1).…”
Section: Cohabitationmentioning
confidence: 97%
“…Rather, it was the influence of the government's "Court Challenges" program that caused a liberal shift on the Court. Epp (1996Epp ( , 1998 argues that it was increases in the support structure for legal mobilization, assisted by increasing judicial docket control that had the greatest impact on the development of a rights agenda on the Court. He argues that the emergence of rights-advocacy organizations, including the Canadian Civil Liberties Association and the Women's Legal Education and Action Fund (LEAF), the increasing expansion of the legal profession-along with its increasing diversification, and increasing funding from federal and provincial governments for legal aid led to the expansion of rights in Canadian society (1996,1998).…”
Section: The Charter Of Rights and Freedoms: 1982mentioning
confidence: 98%